The effect of a mindfulness-based intervention on anxiety and emotional regulation in gifted students - Haneefa, Manar (مجلة جامعة الملك عبدالعزيز: العلوم التربوية والنفسية, 2026)
In order to improve the psychological components of gifted students, various intervention methods have been used. One of these methods is mindfulness training. The aim was to investigate and test the effect of mindfulness intervention on the anxiety and emotional regulation of gifted students. The research method was experimental with a pre-test-post-test design with a control group.